Presetting of the Corticospinal Excitability in the Tibialis Anterior Muscle in Relation to Prediction of the Magnitude and Direction of Postural Perturbations - Fujio, Kimiya; Obata, Hiroki; Kawashima, Noritaka; Nakazawa, Kimitaka (Frontiers in Human Neuroscience, 2019)
The prediction of upcoming perturbation modulates postural responses in the ankle muscles. The effects of this prediction on postural responses vary according to predictable factors. When the amplitude of perturbation can be predicted, the long-latency response is set at an appropriate size for the required response, whereas when the direction of perturbation can be predicted, there is no effect. The neural mechanisms underlying these phenomena are poorly understood. Here, we examined how the corticospinal excitability of the ankle muscles (i.e., the tibialis anterior [TA], the soleus [SOL], and the medial gastrocnemius [MG], with a focus on the TA), would be modulated in five experimental conditions: (1) No-perturbation, (2) Low (anterior translation with small amplitude), (3) High (anterior translation with large amplitude), (4) Posterior (posterior translation with large amplitude), and (5) Random (Low, High, and Posterior in randomized order). We measured the motor-evoked potentials (MEPs) induced by transcranial magnetic stimulation at 50 ms before surface- translation in each condition. The electromyographic (EMG) responses evoked by surface- translations were also measured. The results showed that the TA-MEP amplitude was greater in the High condition (where the largest TA-EMG response was evoked among the five conditions) compared to that in the No-perturbation, Low, and Posterior conditions (High vs. No-perturbation, p < 0.001; High vs. Low, p = 0.001; High vs. Posterior, p = 0.001). In addition, the MEP amplitude in the Random condition was significantly greater than that in the No-perturbation and Low conditions (Random vs. No-perturbation, p = 0.002; Random vs. Low, p = 0.002). The EMG response in the TA evoked by perturbation was significantly smaller when a perturbation can be predicted (predictable vs unpredictable, p < 0.001). In the SOL and MG muscles, no prominent modulations of the MEP amplitude or EMG response were observed, suggesting that the effects of prediction on corticospinal excitability differ between the dorsiflexor and plantar flexor muscles. These findings suggest that the corticospinal excitability in the TA is scaled in parallel with the prediction of the direction and magnitude of an upcoming perturbation in advance.